A Study Of Budget Characteristics In The Annual Budgeting Process: The Case Of Universiti Sains Malaysia - Abd Rahim, Rafizal (2004)
This study attempt to investigate the relationship between budget characteristics that is budget participation, budget communication, budget clarity and measure and monitor and the dependent variable which is budget performance. We also looked at how budget goal commitment can intervened this relationship.